Plants Flowering and Fruiting Behaviour in Alas Purwo National Park, Banyuwangi, East Java - Dewi Ayu Lestari; Agung Sri Darmayanti (Journal of Tropical Biodiversity and Biotechnology, 2020)
Alas Purwo National Park (APNP) is a conservation area with lowland forest type. The adaptation of plants conserved is strongly influenced by environmental factors and the behaviour of flowering and fruiting. The aims of this research were to find the number, species, dominance, and abundance of flowering and fruiting plants, comparison of flowering and fruiting species, and environmental factors affecting the flowering and fruiting time in APNP observation tracks. This study used purposive random sampling in each observation track where flowering and fruiting plants were found. Environmental factors (temperature, humidity, light intensity, soil pH, elevation, and coordinates) in each observation track were measured. Data analysis was conducted using Microsoft Excel and PAST 4.0. statistic program. The behaviour of flowering and fruiting plants species in APNP was unique. There were 90 species of flowering and fruiting plants in APNP from 45 families. Most species often found flowering and fruiting were Orophea enneandra, Polyalthia littoralis and Leea angulata which were scattered in Moto Lele, Patirtan Mas, and Sadengan Savanna. Fruiting plants species were more often found than flowering ones. Temperature and light intensity became the two most affecting environmental factors on flowering and fruiting plants behaviour. The study of flowering and fruiting behaviour is very important for genetic resources conservation and conservation areas management.